Genu Recurvatum Deformity in a Child due to Salter Harris Type V Fracture of the Proximal Tibial Physis Treated with High Tibial Dome Osteotomy. (13th August 2012) - Beslikas, Theodoros; Christodoulou, Andreas; Chytas, Anastasios; Gigis, Ioannis; Christoforidis, John
Abstract : Salter-Harris type V fracture is a very rare injury in the immature skeleton. In most cases, it remains undiagnosed and untreated. We report a case of genu recurvatum deformity in a 15-year-old boy caused by a Salter-Harris type V fracture of the proximal tibial physis. The initial X-ray did not reveal fracture. One year after injury, genu recurvatum deformity was detected associated with significant restriction of knee flexion and limp length discrepancy (2 cm) as well as medial and posterior instability of the joint. Further imaging studies revealed anterior bone bridge of the proximal tibial physis. The deformity was treated with a high tibial dome osteotomy combined with a tibial tubercle osteotomy stabilized with malleolar screws and a cast. Two years after surgery, the patient gained functional knee mobility without clinical instability. Firstly, this case highlights the importance of early identification of this rare lesion (Salter-Harris type V fracture) and, secondly, provides an alternative method of treatment for genu recurvatum deformity.